The Influence of Trust, Religiosity, Income, Promotion, and Quality of Service on the Interests of the Moslem Community in Zakat Through BAZNAS East Kalimantan - Tikawati Tikawati (IAIN Palopo, 2023)
This study aims to determine the effect of the variables of trust, religiosity, income, promotion, and quality of service on interest in tithing at the East Kalimantan National Zakat Agency. Quantitative method with SmartPLS is used to test the hypothesis. The research questionnaire was distributed to 100 respondents in the East Kalimantan region. The results of this study indicate that the variables of trust, service quality, income and religiosity have a significant effect on muzakki's interest in paying zakat at BAZNAS East Kalimantan. Meanwhile, the promotion factor has no significant effect on the interest of the muzakki in zakat at BAZNAS East Kalimantan. These findings are useful for zakat managers, especially BAZNAS East Kalimantan, to focus development on factors that have a significant effect on interest in paying zakat at BAZNAS East Kalimantan.